Laboratory experiment on copper and lead adsorption ability of microplastics - Goh, Patricia Blair; Siriporn Pradit; Prawit Towatana; Somkiat Khokkiatiwong; Ong, Meng Chuan (Penerbit Universiti Kebangsaan Malaysia, 2022)
The persistent presence of microplastics in the marine environment has become a major threat to many marine organisms and this issue continues with heavy metals pollution. Microplastics and heavy metals are commonly categorized in different type of pollutant group and the understanding of interlinkage between these two contaminants is less discovered. During 7 days laboratory controlled experimentation, we examined the heavy metals; copper (Cu) and lead (Pb) adsorption ability of microplastics fragment derived from plastic straws and plastic grocery bags. We found that both microplastic types adsorbed the two heavy metals through exposure to Cu and Pb spiked seawater with different concentrations, respectively. The adsorption kinetics was represented using partition coefficients that resulted in coefficients between the microplastic fragments and water ranged between 5 and 28 for Cu on plastic straws and bags fragment; 3 and 35 for Pb. The adsorption of Cu and Pb both was significantly higher in plastic bag micro fragments, probably due to higher surface area and polarity. Throughout the experiments time expansion, the concentrations of Cu and Pb significantly increased on both microplastic types. The results of consequential interaction between the selected microplastics and heavy metals strongly support the condition of microplastic ability to adsorb heavy metals and act as a vector for heavy metal ions distribution in the marine ecosystem.